Framework for nontargeted investigation of contaminants released by wildfires into stormwater runoff: Case study in the northern San Francisco Bay area. (20th July 2021) - Chang, Daniel; Richardot, William H.; Miller, Ezra L.; Dodder, Nathan G.; Sedlak, Margaret D.; Hoh, Eunha; Sutton, Rebecca
Abstract: Wildfires can be extremely destructive to communities and ecosystems. However, the full scope of the ecological damage is often hard to assess, in part due to limited information on the types of chemicals introduced to affected landscapes and waterways. The objective of this study was to establish a sampling, analytical, and interpretive framework to effectively identify and monitor contaminants of emerging concern in environmental water samples impacted by wildfire runoff. A nontargeted analysis consisting of comprehensive two‐dimensional gas chromatography coupled to time‐of‐flight mass spectrometry (GC × GC/TOF‐MS) was conducted on stormwater samples from watersheds in the City of Santa Rosa and Sonoma and Napa Counties, USA, after the three most destructive fires during the October 2017 Northern California firestorm. Chemicals potentially related to wildfires were selected from the thousands of chromatographic features detected through a screening method that compared samples from fire‐impacted sites versus unburned reference sites. This screening led to high confidence identifications of 76 potentially fire‐related compounds. Authentic standards were available for 48 of these analytes, and 46 were confirmed by matching mass spectra and GC × GC retention times. Of these 46 compounds, 37 had known commercial and industrial uses as intermediates or ingredients in plastics, personal care products, pesticides, and as food additives. Nine compounds had no known uses or sources and may be oxidation products resulting from burning of natural or anthropogenic materials. Preliminary examination of potential toxicity associated with the 46 compounds, conducted via online databases and literature review, indicated limited data availability. Regional comparison suggested that more structural damage may yield a greater number of unique, potentially wildfire‐related compounds. We recommend further study of post‐wildfire runoff using the framework described here, which includes hypothesis‐driven site selection and nontargeted analysis, to uncover potentially significant stormwater contaminants not routinely monitored after wildfires and inform risk assessment. Integr Environ Assess Manag 2021;17:1179–1193. © 2021 SETAC KEY POINTS: Our objective was to establish a sampling, analytical, and interpretive framework to effectively identify and monitor contaminants of emerging concern in environmental water samples impacted by wildfire runoff. A nontargeted analysis consisting of comprehensive two‐dimensional gas chromatography coupled to time‐of‐flight mass spectrometry (GC × GC/TOF‐MS) was conducted on stormwater samples from watersheds impacted by the October2017 Northern California firestorm. Authentic standards were available for 48 of 76 potentially fire‐related compounds identified with high confidence; 46 were confirmed by matching mass spectra and GC × GC retention times, and preliminary examination of potential toxicity indicated limited data availability. Regional comparison suggested that more structural damage may yield a greater number of unique, potentially wildfire‐related compounds.